DRUG CRIME AS A THREAT TO INDONESIA'S NATIONAL SECURITY - Muhammad Rifqi; Ernalem Bangun (The Republic of Indonesia Defense University, 2020)
Drug crime—i.e. narcotic drug abuse, smuggling, and trafficking—is still a serious problem for many countries. In Indonesia, it is perceived as a threat to national security and Indonesians' well-being. It is not surprising, then, if the government of Indonesia declared war on drugs to preserve Indonesia's national security. The systemic measures to address the drugs problem formulated as an integrated program consists of eradication and prevention of drug smuggling and trafficking, and rehabilitation for the victims of drug abuse. This study discusses the implementation of the program as a part of maintaining national security, as well as its constraints and obstacles. Riau Islands Province was chosen as a case study. The data collection was conducted by in-depth interviews, focused group discussion, and literature studies. In analyzing the data, it uses the theory of drug abuse prevention to organize and to interpret the findings. The result of the analysis shows that several obstacles still hinder the effectiveness of the government's efforts in combating drug crime. In the eradication of narcotic drug smuggling and illicit trafficking, the main obstacles manifest in geographical challenges, regulatory constraints, and technological shortcomings. In the prevention of drug crime, the real effectiveness of socialization as the main tool of prevention is hard to be measured and evaluated. In the rehabilitation of drug abuse victims, the main obstacles are the low awareness of the community, the limited availability of counselors and other infrastructures, and the unsupportive legal system.